Continuity and change in medieval East Central Europe
1 online resource (vii, 284 pages)
Keywords: "Continuity and Change in Medieval East Central Europe explores the crucial societal, political, and cultural dynamics that defined medieval East Central Europe during the early and high Middle Ages. Focusing on the historical regions of Bohemia, Hungary, Poland, and Lithuania, the book provides a comprehensive and comparative analysis of this transformative historical period. It gathers the latest perspectives from leading experts, offering nuanced insights into the interactions between power, religion, and social structures. Featuring original chapters from an interdisciplinary team of contributors, this volume delves into specific aspects of medieval East Central Europe. It examines the "dark ages" around 900 AD, the territorial organization of the Piast monarchies, and the evolution of rulership in the Grand Duchy of Lithuania. Other topics include the changing social status of royal servants in Hungary, the role of church and state in societal changes, and the unique concept of twin cathedrals in ecclesiastical architecture. By providing comparative assessments, the book highlights the complex relationship between continuity and change, offering fresh perspectives on the political and cultural transformations that influenced the region's development. Intended for historians and archaeologists interested in medieval societal changes, this volume is also essential for students in history, archaeology, and art history. By presenting cutting-edge research from various language areas and historical schools, the book makes advanced scholarship accessible to English-speaking readers. It serves the Anglophone academic market and engages experts and students within East Central Europe, offering a critical resource for understanding the medieval period's enduring impact on contemporary societies"--